If I die tonight : a novel - Gaylin, Alison (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"Late one night in the quiet Hudson Valley town of Havenkill, a distraught woman stumbles into the police station--and lives are changed forever. Aimee En, once a darling of the 1980s pop music scene, claims that a teenage boy stole her car, then ran over another young man who'd rushed to help. As Liam Miller's life hangs in the balance, the events of that fateful night begin to come into focus. But is everything as it seems? The case quickly consumes social media, transforming Liam, a local high school football star, into a folk hero, and the suspect, a high school outcast named Wade Reed, into a depraved would-be killer. But is Wade really guilty? And if he isn't, why won't he talk?"--Amazon.com.